Emotional eating and sleep quality: How do government-protected children differ from those living with their parents? - Ozturk, Mujgan; Dayi, Taygun; Inanc, Gonca (Springernature, 2025)
Purpose This study aimed to determine the emotional eating and sleep behaviors of protected children and compare them with their peers who live with their parents. Methods The study was conducted with 78 (Group 1: 39 government-protected children vs Group 2: 39 children living with their parents) 10-18-year-old children and adolescents in Northern Cyprus. Each child in Group 2 had to match a government-protected child with similar sociodemographic features and age as well as the same gender. Data were collected through face-to-face interviews with a survey including the Emotional Eater Questionnaire (EEQ), the Pittsburg Sleep Quality Index (PSQI), the Epworth Sleepiness Scale (ESS), and questions related to general background information. Results No difference was found according to EEQ scores, PSQI scores, PSQI sub-scores, sleep quality, ESS scores, and daytime sleepiness between the groups (p > 0.05). However, Group 1 had a significantly longer sleeping time (8.99 +/- 1.69 vs 8.04 +/- 1.67 h) when compared with Group 2 (p: 0.025). For both of the groups, there was a statistically significant positive correlation between ESS and PSQI as well as EEQ and PSQI scores (p < 0.05). Conclusions In this study, it was shown that while government-protected children had longer sleeping time, they had similar emotional eating status and sleep quality with their peers. Also, ESS and EEQ scores were found to be positively correlated with PSQI scores in each group. The sample size of this study is limited, and data were collected by questionnaires. Future studies with larger sample size and observational methods are needed.
Keywords: Emotional eating; Sleep quality; Daytime sleepiness; Orphans; Family-like care